Clustering Blood Types with Leadership Styles in Middle Management of Sharia Banking in The Riau Island - Mulia Sosiady; Ermansyah, Ermansyah (LPPM Universitas Ekasakti, 2024)
This research was conducted with the aim of understanding how leadership based on blood type operates in Sharia banking in the Riau Archipelago. The sample for this study consisted of 12 middle management leaders in Sharia banking in the Riau Archipelago, specifically in the cities of Tanjung Pinang and Batam. The Sharia banking in the Riau Island include BTN Syariah, Bank Riau Kepri Syariah in Batam, and Sharia Banking Indonesia in Tanjung Pinang. The results of the interviews and questionnaires showed that the majority of the samples had blood type O, with six people, while the leadership style at the middle management level was authority compliance management, which prioritizes results or product concentration over people/employees. This is because the leaders believe that when the results are good, the employees' welfare will automatically be good. The most suitable leadership style, after being analyzed based on blood type, is blood type A. Therefore, the research recommendation is that when there is a promotion from staff to middle management level, top management should consider blood type when appointing middle management positions.